Efektivitas Intervensi Pendidikan dan Penggunaan Obat Herbal dalam Mencegah Stunting: Sebuah Studi di Kalangan Kader Kesejahteraan Keluarga di Desa Ababi, Bali - Viviana Bali Sua; I Gusti Ayu Rai Widowati; I.G.N Windra Wartana Putra; I Putu Riska Ardinata; Ida Ayu Manik Partha Sutema (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Stunting remains a public health priority in Indonesia, including in Ababi Village, Karangasem, which has one of the highest stunting prevalence rates in Bali. This study aimed to evaluate the effectiveness of an educational intervention in improving knowledge among family welfare empowerment cadres regarding stunting and the use of herbal medicine for its prevention. A pre-experimental one-group pretest-posttest design was conducted in Ababi Village. The sample consisted of 40 purposively selected cadres who met the inclusion criteria of being active in community health promotion. The research instrument was a validated questionnaire developed based on the World Health Organization’s framework and previous literature, which included items on stunting and the use of herbal medicine for its prevention. The intervention included educational sessions and leaflet distribution. Data were analyzed using the Wilcoxon Signed Rank Test and chi-square test. Results showed that most respondents were aged 23–35 years (37.5%), were housewives (80%), had a primary education level (35%), and belonged to families with four to five members (50%). At baseline, 82.5% of participants had good knowledge of stunting, while only 60% demonstrated good knowledge of herbal medicine use. After the intervention, all respondents (100%) showed good knowledge in both areas, with a statistically significant improvement (p<0.001). Bivariate analysis indicated that occupation was significantly associated with knowledge of stunting (p=0.004), and education level was associated with knowledge of herbal medicine use (p=0.043). In conclusion, the educational intervention effectively improved the cadres’ knowledge about stunting and the use of herbal medicine for its prevention. This study supports the role of pharmacists and health educators in community-based stunting prevention efforts.